The Fitrah, Potential, and Human Development According to Islamic View - Sunarto Sunarto; Desi Nurhabibah; M. Indra Saputra (International Journal on Advanced Science, Education, and Religion, 2024)
This research aims to explore Islamic views on nature, potential and human development, as well as their implications for the practice of Islamic education. By understanding these concepts comprehensively, this research seeks to contribute to formulating an education system that is holistic and oriented towards the welfare of the world and the hereafter. The research method used is library research with a qualitative approach. Data was collected through a review of primary literature such as the Al-Qur'an, Hadith, as well as the works of Islamic education scholars and thinkers. Data analysis was carried out descriptively-analytically to understand the concepts of nature, potential and human development according to an Islamic perspective. The research results show that Islam views humans as creatures born with a sacred nature and extraordinary potential, including physical, intellectual, emotional and spiritual aspects. Islamic education has a major role in exploring and developing this potential, with the aim of forming individuals with Islamic character, faith and noble character. In conclusion, Islamic education based on divine values can be a solution to the moral and spiritual challenges faced by modern society